The cross-sectional distributions of financial ratios: Theory, evidence, and implications - Dunmore, Paul (School of Management Working Papers, 1994)
Simple assumptions about the joint distribution of two accounting variables lead to the conclusion that the tails of the distributions of financial ratios follow power-law rather than exponential forms. Algebraic constraints on the accounting variables are reflected in different forms of the ratio tail distributions. The conclusions are largely supported for twelve ratios from large samples of U.S. manufacturers during 1974-1992; a shift towards greater long-tailedness occurred around 1980. Several statistical techniques which have been commonly performed using financial ratios are unsound because ratios have such long tails. Redefinitions of most financial ratios are proposed which may mitigate the problems.